Comparison of the effects of alpha-methyl-p-tyrosine and a tyrosine-free amino acid load on extracellular noradrenaline in the rat hippocampus in vivo. - McTavish, S; Callado, L; Cowen, P; Sharp, T (1999)
Peripheral administration of an amino acid load lacking tyrosine and its precursor, phenylalanine, causes a lowering of central tyrosine levels. The aim of the present study was to examine the effects of tyrosine depletion on extracellular noradrenaline using microdialysis. Extracellular noradrenaline was measured in hippocampus of the anaesthetized rat under both baseline conditions (with reuptake inhibitor, desipramine, in the perfusion medium) and following administration of the alpha2-adrenoreceptor antagonist, idazoxan. The tyrosine free amino acid load did not alter either baseline noradrenaline or the twofold rise in noradrenaline evoked by idazoxan compared with saline controls. In contrast, the catecholamine synthesis inhibitor, alpha-methyl-p-tyrosine, caused a marked reduction in baseline extracellular noradrenaline and abolished the rise induced by idazoxan. In conclusion, the present data indicate that under the conditions used, a tyrosine-free amino acid mixture may not be an effective means to interfere with central noradrenaline function. This contrasts with recent findings demonstrating that the tyrosine-depletion approach can be used to decrease presynaptic dopamine function.